ANALYSIS OF TEACHER PROBLEMS IN THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN ELEMENTARY SCHOOL NEGERI 1 LAMBHEU, ACEH BESAR DISTRICT - Alviana, Rahma; Safiah, Intan; Fitri, Aida (Universitas Syiah Kuala, 2024)
The implementation of the independent curriculum will be implemented at SD Negeri 1 Lambheu starting in the 2022/2023 school year and will be implemented in stages. In implementing learning, there are problems in planning, implementing and evaluating learning. The problem in this research is